2021
DOI: 10.1094/pdis-02-20-0329-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Lasiodiplodia theobromae Causing Decline of Blueberry (Vaccinium corymbosum) in the Czech Republic

Abstract: Popularity of blueberries (Vaccinium corymbosum L.) has been rising worldwide, due to their nutritional bioactive compounds such as flavonoids, anthocyanins and polyphenols (Sinelli et al. 2008). These factors led to an increase of the demand for fresh blueberries in the Czech market, which resulted in increased blueberry planted in the Czech Republic. In spring 2018, about 200,000 1-year-old blueberry plants originally from the Netherlands were planted on 47 ha in the South Moravian region. In September 2019,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…PDA was frequently used to study the growth characteristics of L. theobromae isolates as this medium composition favored maximum growth of L. theobromae (Latha et al, 2013). L. theobromae isolates grew as irregular shaped colonies with greenish black/grey color and black color in reverse (Pečenka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDA was frequently used to study the growth characteristics of L. theobromae isolates as this medium composition favored maximum growth of L. theobromae (Latha et al, 2013). L. theobromae isolates grew as irregular shaped colonies with greenish black/grey color and black color in reverse (Pečenka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sowmya et al (2018) studied the severity of the BRR disease in major mulberry growing areas of India. The Lasiodiplodia species is known to cause dieback, cankers, and stem and root rot in multiple crops like almonds, blueberry, castor, Chinese hackberry, citrus, cocoa, coconut, grapevines, groundnut, jackfruit, mango, melon, olive, Pinus spp., strawberry, and rice (Bautista-Cruz et al, 2019;Chen et al, 2021;Liang et al, 2019;Nam et al, 2016;Pečenka et al, 2021;Rosado et al, 2016;Saeed et al, 2017).…”
mentioning
confidence: 99%
“…Excluding grapevine, two Botryosphaeriaceae spp. were recently reported causing dieback of highbush blueberry from the Czech Republic, namely, Lasiodiplodia theobromae and Neofusicoccum parvum [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Species of Lasiodiplodia, mostly L. theobromae, are important pathogens of blueberry in tropical and subtropical climates (e.g., Rodríguez-Gálvez et al, 2020), but have been also reported in Europe associated with canker and dieback of highbush blueberry in Spain (Borrero et al, 2019) and the Czech Republic (Pečenka et al, 2021). Macrophomina phaseolina, a common soilborne fungus, has also been reported on highbush blueberry plants, causing charcoal rot in Spain (de los Santos et al, 2019) and blight in Serbia (Popovič et al, 2018).…”
Section: Fungal Trunk Diseases Of Berry Fruitmentioning
confidence: 99%